The special shaped laser spot for driving indirect-drive hohlraum with multi-beam incidence. (30th August 2017) - Li, Ping; Jin, Sai; Zhao, Runchang; Wang, Wei; Li, Fuquan; Li, Mingzhong; Su, Jingqin; Wei, Xiaofeng
Abstract : In indirect drive, reducing peak intensity of a single beam and controlling overlap of multi-beams are two opposite requirements for laser focal spot design. In this paper, an improved laser spot design technique for indirect drive built upon the geometric structures of laser propagation into hohlraum has been introduced. The proposed technique is able to generate appropriate continuous phase plate (CPP) producing a special shaped spot that can balance the opposite requirements. The corresponding CPP does not bring difficulties to the design and fabrication. Phase aberrations are more sensitive to the special shaped spot; however, it can be tolerable for the current beam control level.